Od wiersza do miana – odwrócony(?) porządek. Onomastycznokulturowe konteksty poezji Wisławy Szymborskiej - Rejter, Artur (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article discusses the function of proper names in the poetry of Wisława Szymborska. It falls within the realm of literary and cultural onomastics and draws from the methodological assumptions of these sub-disciplines. The observations confirm the invaluable potential of proper names, used in Szymborska’s poetry to varying degrees and in different functions. The creative poetic techniques applied to proper names, their functions and their relationship to the proper name as a specific linguistic entity are manifold. The poetic recontextualization of proper names in Szymborska’s poetry serves various purposes. Primarily, the described techniques involving proper names fulfill the function of world-building in line with the Nobel laureate’s creative philosophy, perception of reality, sensitivity to it, concern for humanity and its condition, and her expression of attitudes toward tradition and history, as well as continuous maintenance of a sense of wonder about the world. There is also the issue of naming itself, whose markers are used, reformulated or even questioned to varying degrees and senses. All of this confirms the immersion of the studied work in culture, in its various aspects and forms, which is also evident in the onymic layer of the poetic message.